Fluoride Accumulation by Vegetables and Crops Grown in Nawa Tehsil of Nagaur District (Rajasthan, India) - Yashoda Saini2, Radha Gautam1, Nagendra Bhardwaj2 and (Journal of Phytology, 2010)
Fluoride is recognized as an important trace element playing a vital role in the dental and skeletal formation in human beings. It is generally believed that organisms including human being receive fluoride largely from drinking water sources and that the total daily intake of fluoride by individuals from water and other sources varies from country to country depending on the amount of fluoride present in water and other sources including foodstuffs. Earlier it was believed that food was not a rich source of fluoride for humans but it is now well documented that certain types of food can have high fluoride content. Therefore in the present investigation to study the transfer of fluoride from one tropic level to another and accumulation of fluoride in the food chain, food items were collected from nawa tehsil in nagaur district (Rajasthan) and analyzed. Leafy vegetables like spinach, radish leaves, Sarso leaves were analyzed among which spinach (25.70 Âµg/g) showed maximum fluoride concentration. Cereals like barley, wheat, chana, bajra, moth, chawla, methi were also analyzed for fluoride out of which methi and chawla was found to have maximum fluoride concentration (18.98 Âµg/g) which was collected from Shivdanpura village where fluoride concentration in water samples was found in the range between 7.36 ppm to 13.83 ppm. Key words: Fluoride, Foodstuffs, Vegetables, Cereals, Nawa tehsil <span style="font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Radha Gautam et al. Fluoride Accumulation by Vegetables and Crops Grown in Nawa Tehsil of Nagaur District (Rajasthan, India). J Phytol 2/2 (2010) 80-85.